2001
DOI: 10.1086/324340
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Human Orthologue of the Mouse underwhite Gene (uw) Underlie a New Form of Oculocutaneous Albinism, OCA4

Abstract: Oculocutaneous albinism (OCA) affects approximately 1/20,000 people worldwide. All forms of OCA exhibit generalized hypopigmentation. Reduced pigmentation during eye development results in misrouting of the optic nerves, nystagmus, alternating strabismus, and reduced visual acuity. Loss of pigmentation in the skin leads to an increased risk for skin cancer. Two common forms and one infrequent form of OCA have been described. OCA1 (MIM 203100) is associated with mutations of the TYR gene encoding tyrosinase (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
325
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(332 citation statements)
references
References 28 publications
(33 reference statements)
3
325
1
3
Order By: Relevance
“…Human AIM-1 was first identified as a melanoma antigen with unknown function (Harada et al 2001). However, recently, Newton et al (2001) assigned it to the underwhite locus (uw), which tion of non-Caucasians to the present white South African population (Caucasians) is estimated to be about 7% from studies of the HLA human major histocompatibility complex (Botha et al 1975), and this value well accounts for the breakdown of the monomorphic status of Phe (0.89) among the white South Africans in the present study. Newton et al (2001) also reported that L374F is a common polymorphism.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Human AIM-1 was first identified as a melanoma antigen with unknown function (Harada et al 2001). However, recently, Newton et al (2001) assigned it to the underwhite locus (uw), which tion of non-Caucasians to the present white South African population (Caucasians) is estimated to be about 7% from studies of the HLA human major histocompatibility complex (Botha et al 1975), and this value well accounts for the breakdown of the monomorphic status of Phe (0.89) among the white South Africans in the present study. Newton et al (2001) also reported that L374F is a common polymorphism.…”
Section: Introductionsupporting
confidence: 51%
“…However, not a little genetic evidence suggests an intervention of AIM-1 in mammalian pigmentation. The cytogenetic location of human AIM1 (5p13.3, NCBI LocusLink; 51151) does not preclude AIM1 from being a candidate for an important pigmentation locus, uw (Sweet et al 1998), and it was, in fact, proved that the AIM1 is responsible for one type of human albinism (Newton et al 2001). In mice, a double mutation of uw and Mc1r results in significantly less pigmentation than either mutation alone (Lehman et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…29 OCA4 was first defined on presentation in one individual homozygous for a splice-site mutation within the SLC45A2 gene on chromosome 5p, with the phenotype consisting of generalized and ocular hypopigmentation similar to that seen in OCA2 patients. 30 OCA4 is one of the most common forms of albinism in the Japanese population. 31,32 Polymorphism within the SLC45A2 gene is a major determinant of normal variation in skin pigmentation, 33 with the rs16891982 b.1122G/C, p.374Leu/Phe change of the encoded protein, MATP, associated with the lighter pigmentation phenotypes of Europeans.…”
Section: Introductionmentioning
confidence: 99%
“…SLC45A2 mutations have been found in medaka (Fukamachi et al 2001), humans (Newton et al 2001), mouse (Newton et al 2001;Du and Fisher 2002), and horse (Mariat et al 2003). Oculocutaneous albinism type IV (OCA4) in humans is caused by mutations in SLC45A2 (Newton et al 2001).…”
mentioning
confidence: 99%